PEMANFAATAN CANVA DALAM PENGEMBANGAN VIDEO PEMBELAJARAN DI KELAS IV PADA MATERI GAYA DAN GERAK - Nadya Dwi Pramesti; Regina Lichteria Panjaitan; Atep Sujana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop Canva-based video learning media to improve fourth-grade elementary school students' understanding of force and motion. The study used the Research and Development (R&D) method with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects in this study were 31 fourth-grade elementary school students and a media expert as a validator. Data collection was conducted through interviews, media questionnaire validation, and pretest-posttest tests. The media expert validation results indicated that the Canva-based learning video was highly feasible with an average score of 94%. The pretest and posttest analysis results indicated an increase in student understanding, with an average N-Gain score of 0.60, which is in the moderate category. Thus, Canva-based video learning media can be used as an effective interactive learning tool to help students understand the concepts of force and motion in science.